Proteína e qualidade de sementes de feijão (Phaseolus vulgaris L.) em função da adubação nitrogenada em plantio direto - Gomes Junior, Francisco Guilhien; de Sá, Marco Eustáquio [UNESP] (FapUNIFESP (SciELO), 2010)
Nitrogen limitation in the common bean (Phaseolus vulgaris L.) produces reduced productivity and seeds with low protein content and physiological quality. We assessed the effects of nitrogen fertilizer side dressing on the protein content and physiological quality of the seeds of P. vulgaris L. cultivars (cv.) IPR Juriti and Pérola grown in plots (soil type = Dystrophic Red Latosol) using a no-tillage system under a thick mulch of millet residues at the Experimental Station of UNESP-Ilha Solteira campus, located in Selvíria, MS (Köppen climate type = Aw) during autumn (March/June) and winter (June/September) 2005. For each cultivar, a randomized block experimental design was used with four replicates and factorially arranged treatments equivalent to 0, 30, 60, 90 and 120 kg.ha-1 added nitrogen (as urea, containing 45% of N) applied as a side dressing during the V4-3 and V4-6 phenological stage corresponding to the 3rd and 6th completely opened trifoliolate leaf on the main stem. Supplementation with up to 120 kg.ha-1 nitrogen promoted a greater increase in crude protein at V4-3 (unsupplemented = 17.6% and 16.3%; 120 kg.ha-1 N = 24.1% and 22.3% for cv. IPR Juriti and Pérola, respectively) than at V4-6 (unsupplemented = 19.2% and 18.3%; 120 kg.ha-1 N = 21.3% and 20.3% for cv. IPR Juriti and Pérola, respectively). About 90% of the crude protein from cv. IPR Juriti was composed of soluble protein compared to 72% for the cv. Pérola. Albumins and globulins represented about 80% of the soluble protein and prolamins were lower at 0.6%. In conclusion, nitrogen fertilization up to 120 kg.ha-1 applied as a side dressing at the V4-3 phenological stage in no-tillage under a thick mulch of millet promoted a greater increase of crude protein in common bean seeds than at the V4-6 stage. The highest accumulation of soluble protein occurred at 90 kg.ha-1 applied nitrogen without having a significant influence on the physiological quality of the seeds.
Protein content and common bean (Phaseolus vulgaris L.) seed quality in relationship to nitrogen fertilization in a no-tillage system
Keywords: Albumins; Glutelins; Physiological quality; Soluble protein; Phaseolus vulgaris